Effect of work environment and work discipline on employee performance (case study at UPTD Tunggak Jati health center) - Shilma; Budi Rismayadi; Neni Sumarni (Trigin Publisher, 2022)
The purpose of this study is to determine the work environment and work discipline on employee performance so that they have good performance. This type of research is quantitative. The population in this study were 44 employees. The data collection technique used in this study was by distributing questionnaires to employees of the Tunggak Jati Health Center. Also by using interviews and observations. The sample was taken with a saturated sample because the total population was below 100. Where the population was only 30 so that all populations were sampled, the method used was multiple regression analysis, with the help of SPSS 25 software. The results obtained Fcount of 1,655 and greater than the value of Ftable 3.33 and a significant value of 0.210 which is greater than 0.05. This indicates that the research results are accepted by H₀. Simultaneously, the work environment and work discipline have a positive but not significant effect on employee performance at the UPTD Puskesmas Tunggak Jati Kab. Karawang